Biodiversity studies of medical herb Epimedium Sagittatum (TCM herb 淫羊藿) - Peh, William Wei Liang. (2010)
Epimedium Sagittatum is a wild-crafted perennial Traditional Chinese Medicine (TCM) herb mainly distributed in Southern China and is used to treat Ying/yang [阴阳] problems. 384 samples of 25 populations belonging to 3 sub-species of Epimedium Sagittatum from 21 counties/cities in 6 China provinces were genotyped with 7 highly polymorphic Simple Sequence Repeat (SSR) loci. 239 alleles detected revealed 100.0% polymorphism with mean observed heterozygosity HO of 0.601 suggesting a high level of diversity. Mantel test (Regression value R2 of 0.055) found weak correlation between genetic distances and geographical distances among populations. AMOVA test for sub-species showed that 96% of total genetic variation was within traditionally classified subspecies and principle coordinate analysis (PCA) revealed no obvious clustering of subspecies, all indicating the lack of genetic basis for such classification. Phylogenetic tree of the populations based on Nei genetic identity was constructed. With mean genetic similarity of only 0.296, all the populations are distinct from each other. Such genetic divergence may underline phytochemical divergence, which was confirmed by the big variation of icarrin, the marker compound for Epimedium. Genetic similarity was not correlated with phytochemical similarity for icariin. Implications of this finding on quality control of Epimedium are discussed.